Pemikiran Pendidikan Islam Ibnu Maskawaih - Napitupulu, Dedi Sahputra (Al-Riwayah : Jurnal Kependidikan, 2019)
This paper describes the educational thought about Islam Ibn Maskawaih. Although Ibn Maskawaih is an expert on the philosophy of morals, but it turns out that if traced further, he also had a brilliant thinking in the field of education, particularly in the field of Islamic education. It is evident that his philosophycal ideas that introduces in Islamic education are the reference of Muslim and Western scientists. The educational concept of Ibn Maskawaih related to the purpose of education which makes the capability of inner attitude to spontaneously give birth to all deeds of good-value. Thus thorough perfection and true happiness (assa’adah ) of human life are achieved. By using the library's analysis of this paper explains about the biography of Ibn Maskawaih, his works, the concept of the human being and ethics and the concept of education according to Ibn Maskawaih.